Free thyroxine, brain frailty and clock drawing test performance in patients with acute minor stroke or transient ischaemic attack. (26th July 2021) - Guo, Zhiliang; Xu, Guoli; Wang, Ruojun; Hou, Jie; Yu, Shuhong; Wang, Huaishun; Yu, Shuai; Xu, Jiaping; You, Shoujiang; Huang, Zhichao; Xiao, Guodong; Cao, Yongjun; et al.
Abstract: Objective: Thyroid dysfunction is associated with an elevated risk of cognitive decline, but the mechanism underlying this relationship is elusive. In this study, we investigate the relationships between free thyroxine (FT4), brain frailty and clock drawing test (CDT) performance in patients with acute minor stroke or transient ischaemic attack (TIA). Design, Patients and Measurements: A total of 204 consecutive patients admitted to our hospital within 72 h after the onset of acute minor stroke or TIA were prospectively enroled and categorized in terms of quartiles of FT4 between March 2018 and August 2019. Brain frailty on magnetic resonance imaging was rated according to previously published criteria. Cognitive performance was assessed with the CDT. Results: Generalized linear analysis revealed that FT4 was independently associated with higher brain frailty score after adjusting potential confounders ( β, 0.03; 95% confidence interval [CI], 0.00–0.06; p  = 0.0205), which is consistent with the result of FT4 (quartile) as a categorical variable ( β, 0.34; 95% CI, 0.01–0.68; p  = 0.0059; p trend  = 0.0807). A nonlinear relationship was detected between FT4 and brain frailty score, which had an inflection point of 1.19. FT4 was also associated with poor CDT performance (odds ratio, 1.15; 95% CI, 1.04–1.26; p  = 0.0051). And mediation analysis found that brain frailty partially mediated the positive relationship between FT4 and poor CDT performance (indirect effect = 0.0024; 95% CI, 0.0003–0.01, p  = 0.04). Conclusions: Our findings suggested that a higher FT4 level was associated with a higher brain frailty score and poorer CDT performance, and brain frailty might play an important effect on the association between FT4 and cognitive decline.